What the words do not say: SFS for children under the light of social semiotic theory case study: 'Horis sosivio'1. Issue 3 (2nd October 2017) - Dermata, Katerina; Skarpelos, Yannis
Abstract: The research on short stories for children has focused in Greece mostly on their literary, pedagogical, linguistic and educational aspects. This paper attempts to approach Short Form Stories for children under the light of social semiotics, the main elements being the author's choices in sign-creation process and its interpretation by the reader. In the case of short stories, the recipient is the child, who for the first time tries to decode without help the verbal text and to enter - symbolically but also in reality – to the literate society. This moment of the reader's first encounter with a multimodal text is crucial to her/his future reading behaviour. The paper examines the concept of the 'Horis sosivio' (without lifejacket) series, as evidenced at the level of visual design and the combination of text and image for the construction of meaning, as well as the interpretation of the visual text by preschool children as participants in meaning production.